Simulasi Daya Dukung Lahan Agropastura dalam Mendukung Sistem Produksi Sapi Potong - Haba Ora, Fellyanus (Penerbit Goodwood, 2026)
Abstract Purpose: This study aimed to simulate the carrying capacity of existing agropastures to support cattle production systems. Research Methodology: Research materials consisted of forage vegetation in agropasture and 120 farmers respondents. This research was descriptive in nature and had a cross-sectional design. The data include both primary and secondary sources. Data collection techniques were conducted through observations and documentation. Data analysis was performed using Powersim to simulate a nine-year projection. Results: A nine-year simulation projected a significant degradation of the cattle population, resulting in excess forage availability in agropasture. Biophysically, agropasture on Timor Island has an adequate carrying capacity; however, this potential is not optimally utilized due to inefficiencies in the cattle production system, including high mortality rates of calves and adult cattle, low reproductive performance of female cattle, cattle removals that disregard regional carrying capacity, and a high incidence of livestock disease outbreaks. Conclusions: The existing conditions and carrying capacity of feed quantity in the agropasture of Timor Island are very low to support the cattle production system, resulting in overgrazing and disruptions to livestock production and health. If this condition persists, it will lead to the degradation of the cattle population, although it may eventually be followed by excess forage availability. Limitations: This study did not present a dynamic system intervention simulation of the existing carrying capacity of agropastures to support the cattle production system. Contributions: This research contributes to the planning and policy aspects of agroecosystem-based area development, particularly agropasture, in supporting livestock production systems.